PRACTICAL ASPECTS OF THE STRATEGY IMPLEMENTATION FOR REGIONAL AND LOCAL INNOVATION SYSTEMS DEVELOPMENT - Riapukhina, Viktoriia N.; Nikolaevich Glagolev, Sergey; Viktorovna Suprun, Emiliya; Pavlovich Taburchak, Peter (Journal of Applied Engineering Science, 2014)
Many authors have turned their research interests to the problem of innovative development as a result of global trends that have led to the transition to an innovative functioning of an economy. This research focuses on territorial innovation systems represented by the regions and municipalities. The major aim of the study has several objectives associated with the theoretical analysis of practical aspects of the problem in regional and municipal levels. First of all, there is a need to provide a critical review of the literature devoted to innovative development of regional systems. Secondly, the role of territorial authorities in an innovation process is needed to be examined. Finally, this study has an overarching objective to identify the opportunities and evaluation mechanisms for innovation potential of regions and municipalities, as well as to formulate a complex of measures for its development. Basis of this work amounted to actual works of Russian and foreign scientists, the analysis of the Russian experience of innovation, as well as the recommendations of foreign experts. The research is based on Russian and international academic literature, innovation–related articles, the analysis of Russian innovative experience as well as the foreign experts' recommendations related to the issue.
Keywords: Special economic zone; Cluster; Municipality; District; Innovation development; Innovation systems; Innovation